PENGARUH FAKTOR BIOGRAFIS TERHADAP PENGETAHUAN, PEMANFAATAN DAN ADOPSI TEKNOLOGI SUMBER BELAJAR DIGITAL SPASIAL OLEH GURU GEOGRAFI DI KARANGANYAR - Muslihah Juwita Hapsari; Wahyu Widiyatmoko; Siti Azizah Susilawati (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2025)
This study aims to determine whether biographical factors such as age, gender, highest education, and years of teaching experience influence the use of spatial-based digital learning resources by geography teachers in Karanganyar Regency. This quantitative research used a comparative design. The research population includes all geography teachers in Karanganyar Regency, with a sample of 34 geography teachers. Data collection was done using a questionnaire, and data analysis employed descriptive analysis and one-way ANOVA tests. The results showed that biographical factors do not influence the knowledge, utilization, and adoption of spatial digital learning technologies by geography teachers. The highest levels of knowledge, utilization, and adoption of spatially-based digital learning resource technologies are found among teachers aged 20-30 years, male teachers, and those with a Bachelor's degree. Regarding teaching experience, knowledge of spatially-based digital learning resources is highest among teachers with 5-10 years of experience, the utilization of spatially-based digital learning resources is highest among teachers with 16-20 years of experience, and the adoption of spatially-based digital learning resource technologies is highest among teachers with 21-25 years of experience. Continuous training or development related to knowledge, utilization, and adoption of spatially-based digital learning resource technologies for geography teachers does not differentiate based on biographical factors such as age, gender, highest education level, or teaching experience